Non-physician Clinicians in Sub-Saharan Africa and the Evolving Role of Physicians - Nir Eyal; Corrado Cancedda; Patrick Kyamanywa; Samia A. Hurst (Kerman University of Medical Sciences, 2016)
Responding to critical shortages of physicians, most sub-Saharan countries have scaled up training of nonphysician clinicians (NPCs), resulting in a gradual but decisive shift to NPCs as the cornerstone of healthcare delivery. This development should unfold in parallel with strategic rethinking about the role of physicians and with innovations in physician education and in-service training. In important ways, a growing number of NPCs only renders physicians more necessary - for example, as specialized healthcare providers and as leaders, managers, mentors, and public health administrators. Physicians in sub-Saharan Africa ought to be trained in all of these capacities. This evolution in the role of physicians may also help address known challenges to the successful integration of NPCs in the health system.